Reproducibility and accuracy of linear measurements on dental models derived from cone-beam computed tomography compared with digital dental casts - de Waard, Olivier; Rangel, Frits Andreas; Fudalej, Piotr Stanislaw; Bronkhorst, Ewald Maria; Kuijpers-Jagtman, Anne Marie; Breuning, Karel Hero (American journal of orthodontics and dentofacial orthopedics, 2014)
INTRODUCTION: The aim of this study was to determine the reproducibility and accuracy of linear measurements on 2 types of dental models derived from cone-beam computed tomography (CBCT) scans: CBCT images, and Anatomodels (InVivoDental, San Jose, Calif); these were compared with digital models generated from dental impressions (Digimodels; Orthoproof, Nieuwegein, The Netherlands). The Digimodels were used as the reference standard. METHODS: The 3 types of digital models were made from 10 subjects. Four examiners repeated 37 linear tooth and arch measurements 10 times. Paired t tests and the intraclass correlation coefficient were performed to determine the reproducibility and accuracy of the measurements. RESULTS: The CBCT images showed significantly smaller intraclass correlation coefficient values and larger duplicate measurement errors compared with the corresponding values for Digimodels and Anatomodels. The average difference between measurements on CBCT images and Digimodels ranged from -0.4 to 1.65 mm, with limits of agreement values up to 1.3 mm for crown-width measurements. The average difference between Anatomodels and Digimodels ranged from -0.42 to 0.84 mm with limits of agreement values up to 1.65 mm. CONCLUSIONS: Statistically significant differences between measurements on Digimodels and Anatomodels, and between Digimodels and CBCT images, were found. Although the mean differences might be clinically acceptable, the random errors were relatively large compared with corresponding measurements reported in the literature for both Anatomodels and CBCT images, and might be clinically important. Therefore, with the CBCT settings used in this study, measurements made directly on CBCT images and Anatomodels are not as accurate as measurements on Digimodels.
Keywords: Dental Impression Technique; zuby; Reproducibility of Results; zobrazování trojrozměrné; počítačová tomografie s kuželovým svazkem; počítačové zpracování obrazu; Image Processing, Computer-Assisted; Software; reprodukovatelnost výsledků; Cone-Beam Computed Tomography; lidé; Models, Dental; Dental Arch; zubní korunka (anatomie); Tooth; kefalometrie; Surface Properties; Cephalometry; zubní oblouk; povrchové vlastnosti; Humans; Tooth Crown; Imaging, Three-Dimensional; software; zubní technika otisková; zubní modely